(untitled) (Journal of Hama University, 2022)
The aim of the research is to evaluate the effectiveness of relying on the behavioral portfolio theory to optimize portfolios’ in line with the investors’ objectives in Damascus Stock Exchange, in order to maximize their final wealth, by adopting different approaches, in addition to determining the characteristics of each portfolio. The study is based on a series of historical and predictive stock data for a group of stocks listed on the DSE during the period from 20/2/2019 to 3/3/2021, being a relatively recent period. We reached to prove the effectiveness of the bootstrapping method in estimating expected future returns that fit with the conditions to be applied for portfolios’ optimization. The differences between the applied theories also affect the characteristics of portfolios, despite the vast differences between theoretical structures and applied methods, which produced optimal portfolios with different characteristics, but the reciprocal relationship between returns and risks and between the investor’s behavioral trends and probabilistic expectations remains indisputably clear. The three approaches (MPT), (CPT) and (BPT) are integrated with each other when forming the behavioral portfolio specifically, as it was clarified by using the weighting function of the prospect theory to calculate the cumulative returns, in addition to using the mathematical programming model of the modern portfolio theory in determining optimum investment weights within the sub-portfolio of the behavioral portfolio that led to logical and consistent results, which establishes the scientific addition of this study.